Benefits of A2 Milk for Sports Nutrition, Health and Performance - Kaplan, Merve; Baydemir, Barış; Günar, Bilgetekin Burak; Arslan, Ayşenur; Duman, Hatice; Karav, Sercan (Frontiers in Nutrition, 2022)
Bovine milk is one of the best pre-and pro-workout sources for athletes owing to its rich nutritional content. Even though bovine milk consumption significantly benefits athletes’ health and performance, many athletes cannot consume bovine milk since they struggle with gastrointestinal problems caused after milk consumption. Especially, the consumption of regular milk, which contains A1 β-casein, is associated with a variety of diseases ranging from gastrointestinal discomfort to ischemic heart diseases. The main reason behind this is related to β-casomorphine 7 (BCM-7), which is derived from A1 β-casein during the digestion of A1 milk. A1 β-casein is formed as a result of a point mutation in the position of 67th in the amino acid sequence A2 β-casein by changing proline to histidine. Therefore, this mutated form of β-casein in regular milk cannot easily be digested by the human-associated digestion enzymes. A2 milk, which includes A2 β-casein instead of A1 β-casein, is the best substitute for regular milk with the same nutritional content. This natural form of milk positively affects the athlete’s health as well as performance without causing any gastrointestinal discomfort or more serious problems which are seen in the consumption of regular milk. In this review, A2 milk and its potential health effects in comparison to diseases related to A1 milk consumption are discussed.